Implementation of Fairness Measures: Systems-of-Systems Governance: A Systematic Mapping of the Literature - Andrade Martins Morais, Edison; Araújo de Lima, Eliomar; Vicente Graciano-Neto, Valdemar (iSys - Journal of Information Systems, 2024)
Systems-of-Systems (SoS) Governance refers to the structure, processes and policies established to manage and coordinate a set of interconnected systems that work together to achieve common goals. Due to the nature of both areas (Governance and SoS), and the possible inherent interaction between them, it is assumed that there are benefits arising from the application of governance principles in SoS. In this sense, the main contribution of this article is the presentation of the results of a systematic mapping that illustrates this application. For this purpose, a protocol was used that prescribes the automatic search in six databases that returned 804 studies, of which 40 were included for analysis, the results of which show that (i) Governance in SoS is a concept already defined in the literature, and helps to ensure that the constituent systems are integrated effectively, and that the SoS as a whole achieves its objectives, (ii) only 14 of the 40 (35%) included studies show the application of Governance in SoS in practice, which shows a difficulty in institutionalizing governance principles in SoS scenarios, which could be research material, (iii) none of the studies included shows how to evaluate the use of governance in SoS.